Controlling the Activities of the Diiron Centre in Bacterial Monooxygenases: Lessons from Mutagenesis and Biodiversity. Issue 21 (2nd April 2015) - Nichol, Tim; Murrell, J. Colin; Smith, Thomas J.
Abstract: The soluble diiron monooxygenases (SDIMOs) are a diverse group of bacterial enzymes that possess a deeply buried binuclear iron centre that forms an oxo‐diferryl (Fe IV ) intermediate that is capable of oxygenating a wide range of unfunctionalised hydrocarbons and other hydrophobic organic molecules, ranging in size from methane to diaromatics such as naphthalene and substituted biphenyls. In the environment, these enzymes are important in bioremediation of hydrocarbons and chlorinated hydrocarbons and in mitigation of the greenhouse effect due to methane, and also have numerous potential applications in synthetic organic chemistry. In this review we consider how both natural variations among the enzymes and an increasing body of evidence from mutagenesis studies cast light on how the protein controls the size of substrates that can access the active site, the precision of regio‐ and stereoselectivity and the oxidising power of the active centre. Abstract : The soluble diiron monooxygenases (SDIMOs) are a diverse group of enzymes that use a diiron active centre to add oxygen to a wide range of organic molecules. Here we review how natural biodiversity and laboratory mutagenesis studies have revealed how the protein scaffold of SDIMOs controls the activity of the enzymes and the presentation of substrates to the diiron site.